PENGARUH AKRUAL DAN KEPEMILIKAN MANAJERIAL TERHADAP RISIKO LITIGASI - Ari Purwanti (Media Riset Akuntansi, Auditing & Informasi, 2017)
This study aims to investigate the effect of accruals on the occurrence of litigation risk. The higher accruals made by managers are thought to cause high litigation risks as well. Therefore, in this study will also see the effect of managerial ownership on the occurrence of litigation risk. Using a sample of consumer goods industries that often experience litigation, testing is done on 37 companies from 2012 until 2016. The results of this study proves that by using multiple regression, developed hypothesis proved that accruals and managerial ownership have a significant positive effect on litigation risk.